On the Hölder property for functions from the class $B_{q, s}$ - Skrypnik, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A class of functions $B_{q, s}$ containing generalized solutions of some higher-order quasilinear parabolic equations is defined. We prove that $B_{q, s}$ is imbedded in the space of Hölder functions.